Аntibacterial inorganic agents: efficiency of using multicomponent systems - А. A. Meleshko (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
Metal and metal oxide nanoparticles (NPs) are promising antibacterial agents. They have a broad antimicrobial activity against both Gram-positive and Gram-negative bacteria, viruses, and protozoans. The use of NPs reduces the possibility of the microbial resistance development. This review briefly shows the general mechanisms and the main factors of antibacterial activity of NPs. In this article, a comprehensive review of the recent researches in the field of new antimicrobial agents with superior long-term bactericidal activity and low toxicity is provided. The review gives the examples of synthesis of double and triple nanocomposites based on following oxides: CuO, ZnO, Fe3O4, Ag2O, MnO2, etc. including metal and nonmetal doped nanocomposites (for example with Ag, Ce, Cr, Mn, Nd, Co, Sn, Fe, N, F, etc.). Compared with bactericidal action of individual oxides, the nanocomposites demonstrate superior antibacterial activity and have synergistic effects. For example, the antimicrobial activity of ZnO against both Gram-positive and Gram-negative bacteria was increased by -100% by formation of triple nanocomposites ZnO—MnO2—Cu2O or ZnO—Ag2O—Ag2S. Similar effect was showed for Ce-doped ZnO and Zn-doped CuO. The present article also provides the examples of nanocomposites containing NPs and organic (chitosan, cellulose, polyvinylpyrrolidone, biopolymers, etc.) or inorganic materials with special structure (graphene oxide, TiO2 nanotubes, silica) which demonstrate controlled release and longterm antibacterial activity. All of the considered nanocomposites and their combinations have a pronounced long-term antimicrobial effect including against antibiotic-resistant strains. They are able to prevent the formation of microbial biofilms on biotic and abiotic surfaces, have low toxicity to eukaryotic cells, demonstrate anti-inflammatory and woundhealing properties in compositions with polymers (sodium alginate, collagen, polyvinylpyrrolidone, etc.). The use of nanoscale systems can solve several important practical problems at the same time: saving of long-term antimicrobial activities while reducing the number of compounds, creation of new antimicrobial agents with low toxicity and reduced environmental impact, development of new biocidal materials, including new coatings for effective antimicrobial protection of medical devices.